New “clinical pearls” on medical practice - Alfredo Espinosa Brito (Medisur)
New “clinical pearls” about medical practice are presented (phrases that, in relatively few words, in a brief, concise and coherent manner, include knowledge or useful advice about the profession), transmitted from “experts” to students and young colleagues “in a “master-apprentice”. These “clinical pearls”, generally, are the result of careful observation and the well-used experience of colleagues, which synthesize knowledge that is passed from generation to generation empirically, just as popular knowledge is transmitted through saying, aphorisms, proverbs, etc. The “original” clinical pearls are transmitted “orally”, from person to person regarding various situations that arise during the exercise of the profession in different scenarios, especially healthcare. Although some clinical pearls could serve as starting points for future full-fledged researches, it must be remembered that in medicine not everything is knowledge, it is also art and ethics. After reflecting again on the role in medical education of these “drops of knowledge”, so in line with the fast times that we live in and with the possibility of having rescued a few more clinical pearls, in this work more than 40 “new” ones are presented, classified as clinical, therapeutic and public health and medical ethics, which are expected to be of practical use in our professionals practice and for the benefit of our citizens.